2014
DOI: 10.1186/s12917-014-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of administration route and dose escalation on plasma and intestinal concentrations of enrofloxacin and ciprofloxacin in broiler chickens

Abstract: BackgroundThe (mis)use of fluoroquinolones in the fowl industry has led to an alarming incidence of fluoroquinolone resistance in pathogenic as well as commensal bacteria. Next to simply reducing antimicrobial consumption, optimizing dosage regimens can be regarded as a suitable strategy to reduce antimicrobial resistance development without jeopardizing therapy efficacy and outcome. A first step in order to limit antimicrobial resistance is to assess the exposure of the intestinal microbiota to enrofloxacin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
1
22
0
3
Order By: Relevance
“…Moraru et al ( 31 ) detected enrofloxacin concentrations in excreta samples ranged between 40.5 and 50.7 μg/g after 3 days orally treatment with 10 mg enrofloxacin/kg BW. Devreese et al ( 26 ) found enrofloxacin concentrations in cloacal samples ranged between 20.1 and 55.7 μg/g after orally treatment of 10 mg enrofloxacin/kg BW. In this study, we found the enrofloxacin concentrations in the intestinal contents were significantly less than previously reported concentrations that maybe due to sample and dosage differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moraru et al ( 31 ) detected enrofloxacin concentrations in excreta samples ranged between 40.5 and 50.7 μg/g after 3 days orally treatment with 10 mg enrofloxacin/kg BW. Devreese et al ( 26 ) found enrofloxacin concentrations in cloacal samples ranged between 20.1 and 55.7 μg/g after orally treatment of 10 mg enrofloxacin/kg BW. In this study, we found the enrofloxacin concentrations in the intestinal contents were significantly less than previously reported concentrations that maybe due to sample and dosage differences.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of enrofloxacin to ciprofloxacin in broilers is limited to 5 and 10% ( 23 , 24 ). There is some research on the PK of enrofloxacin in intestinal contents ( 25 , 26 ), but limited data are available regarding the PK/PD in broiler intestinal contents.…”
Section: Introductionmentioning
confidence: 99%
“…First, the effect size was higher in rat studies than in mouse studies, which suggests that different species may react differently to ginsenoside. Second, the route of administration and dosage of ginsenoside also affected the outcome [ 42 ]. The protective effect on acquisition memory was better with doses of 30 mg or higher (although not significantly) and the protective effect on retention memory was better with doses of 10 mg.…”
Section: Discussionmentioning
confidence: 99%
“…From a risk perspective, greater attention to oral administration practices may be more useful, although this should be confirmed empirically for different antibiotics and animals. For example, Devreese et al (2014) found similar concentrations of enrofloxacin in the cecum and colon of broiler chickens that were treated orally or by intramuscular injection. Unexpectedly higher concentrations were present in the cloaca after systemic injection compared with oral administration.…”
Section: Route Of Administrationmentioning
confidence: 92%